2016
DOI: 10.1037/xhp0000138
|View full text |Cite
|
Sign up to set email alerts
|

Altercentric interference in level 1 visual perspective taking reflects the ascription of mental states, not submentalizing.

Abstract: A growing body of work suggests that in some circumstances, humans may be capable of ascribing mental states to others in a way that is fast, cognitively efficient, and implicit (implicit mentalizing hypothesis). However, the interpretation of this work has recently been challenged by suggesting that the observed effects may reflect "submentalizing" effects of attention and memory, with no ascription of mental states (submentalizing hypothesis). The present study employed a strong test between these hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
206
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(246 citation statements)
references
References 30 publications
16
206
8
2
Order By: Relevance
“…The data also revealed an egocentric intrusion effect, whereby participants did not ignore their own perspective when required to simulate the viewpoint of a distant avatar [2426,42]. Finally, our data indicate that altercentric and egocentric intrusion effects exist in participants older (mean age 66 years old) than previously tested healthy populations (e.g., mean age was 21 in Ref.…”
Section: Discussionsupporting
confidence: 54%
“…The data also revealed an egocentric intrusion effect, whereby participants did not ignore their own perspective when required to simulate the viewpoint of a distant avatar [2426,42]. Finally, our data indicate that altercentric and egocentric intrusion effects exist in participants older (mean age 66 years old) than previously tested healthy populations (e.g., mean age was 21 in Ref.…”
Section: Discussionsupporting
confidence: 54%
“…There is already evidence that automatic visual perspective taking (Samson et al 2010) and some other automatic social processes can be influenced by knowledge about whether the protagonist who is the target of these processes can see or not (e.g., Furlanetto et al 2015;Teufel, Fletcher, and Davis 2010). These effects do not entail that representations from flexible mindreading form direct inputs to more efficient mindreading processes, but we see no decisive reason in theory why even this should be ruled out under appropriately limited circumstances.…”
mentioning
confidence: 65%
“…Adults were slower and more prone to errors in judging how many dots they could see when the avatar's perspective differed from theirs. Another study confirmed that adults experienced interference from the avatar's perspective only if they believed he could see, suggesting that interference resulted from processing of the avatar's mental states, not merely from seeing the direction he faced (cf. ).…”
Section: Signature Limits On Efficient Mindreadingmentioning
confidence: 88%